Follow-up after acute poisoning by substances of abuse: a prospective observational cohort study - Vallersnes, Odd Martin (Scand J Prim Health Care, 2016)
OBJECTIVE: To chart follow-up of patients after acute poisoning by substances of abuse, register whether patients referred to specialist health services attended, and whether patients contacted a general practitioner (GP) after the poisoning episode. DESIGN: Observational cohort study. SETTING: A primary care emergency outpatient clinic in Oslo, Norway. SUBJECTS: Patients ≥12 years treated for acute poisoning by substances of abuse were included consecutively from October 2011 to September 2012. MAIN OUTCOME MEASURES: Follow-up initiated at discharge, proportion of cases in which referred patients attended within three months, and proportion of cases in which the patient consulted a GP the first month following discharge. RESULTS: There were 2343 episodes of acute poisoning by substances of abuse. In 391 (17%) cases the patient was hospitalised, including 49 (2%) in psychiatric wards. In 235 (10%) cases the patient was referred to specialist health services, in 91 (4%) advised to see their GP, in 82 (3%) to contact social services, in 74 (3%) allotted place in a homeless shelter, and in 93 (4%) other follow-up was initiated. In 1096 (47%) cases, the patient was discharged without follow-up, and in a further 324 (14%), the patient self-discharged. When referred to specialist health services, in 200/235 (85%) cases the patient attended within three months. Among all discharges, in 527/1952 (27%) cases the patient consulted a GP within one month. When advised to see their GP, in 45/91 (49%) cases the patient did. CONCLUSION: Attendance was high for follow-up initiated after acute poisoning by substances of abuse. KEY POINTS: Despite poor long-term prognosis, patients treated for acute poisoning by substances of abuse are frequently not referred to follow-up. Nearly all patients referred to specialist health services attended, indicating the acute poisoning as an opportune moment for intervention. Advising patients to contact their GP was significantly associated with patients consulting the GP, but few patients were so advised. One out of three patients was discharged without follow-up, and there seems to be an unused potential for GP involvement.